Ensino de ciências e mudanças tecnológicas: do dilema limitante à construção humanizadora no IF Baiano campus Santa Inês - Silva, Cleber de Souza (Universidade Federal de São Carlos, 2025)
The contradictory role made to technology in modern times, of satisfying human needs while simultaneously being a means of reproducing oppression/exclusion, contrasts with the representation of the neutral and evolutiove application of scientific knowledge still present in Brazilian schooling. By defending the humanizing relationship, we seek to answer the question: what are the relationships between science teaching at IF Baiano, Santa Inês campus, and the technological changes in the living space of this community, established by subjects of scientific and technological education? We highlight the scientificist-technicist dilemma as a discursive practice organizing science teaching at the institution, and we discuss its historical roots. The dialogue between the studies of Dussel (1984), Feenberg (2010), and Santos (2002) included decisive elements in reaffirming the importance of a rupture in the meanings of technology shared by the subjects of education. We designed and carried out an ethical-critical curricular exercise based on the principles and guidelines of Freirean Thematic Investigation, the Curricular Restructuring Movements, and Critical Collaborative Research. In the thematic network produced, we observed the feasibility of the humanizing relationship between science teaching and local/global technological changes. Despite the regionalized limit situations, namely, the naturalization of productivism, clientelism and discrimination, bringing together significant statements that articulate the technological dimension, there was no consensus among educators about the contributions of science teaching. Finally, we highlight changes in ethics admitted by the collaborative research group, from an initial consensus to a conflict of positions about the best curricular orientation for science teaching.

El papel contradictorio que desempeña la tecnología en los tiempos modernos, satisfaciendo necesidades humanas y al mismo tiempo siendo un medio para reproducir la opresión y la exclusión, contrasta con la representación de la aplicación neutral y evolutiva del conocimiento científico aún presente en la escolaridad brasileña. Al defender la relación humanizadora, buscamos responder a la pregunta: ¿cuáles son las relaciones entre la enseñanza de ciencias en el IF Baiano campus Santa Inês y los cambios tecnológicos en el espacio vital de esta comunidad, establecidos por sujetos de educación científica y tecnológica? Destacamos el dilema cientificista-tecnicista como práctica discursiva que organiza la enseñanza de las ciencias en la institución, sobre la cual discutimos sus raíces históricas. El diálogo entre los estudios de Dussel (1984), Feenberg (2010) y Santos (2002) destacó elementos decisivos para reafirmar la importancia de una superacion en los significados de la tecnología compartidos por los sujetos de la educación. Diseñamos y ejecutamos un ejercicio curricular ético-crítico basado en los principios y lineamientos de la Investigación Temática Freireana, los Movimientos de Reestructuración Curricular y la Investigación Crítica Colaborativa. Observamos en la red temática producida, la factibilidad de la relación humanizadora entre la enseñanza de las ciencias y los cambios tecnológicos locales/globales. A pesar de que las situaciones límite regionalizadas, a saber, la naturalización del productivismo, el clientelismo y la discriminación, congregaron discursos significativos que articulan la dimensión tecnológica, no hubo consenso entre los educadores sobre los aportes de la enseñanza de las ciencias. Finalmente, destacamos los cambios en la ética admitidos por el grupo de investigación colaborativo, desde un consenso inicial a un conflicto de posiciones respecto de la mejor orientación curricular para la enseñanza de las ciencias.
Science teaching and technological changes: from the limiting dilemma to the humanizing construction at IF Baiano campus Santa Inês
Enseñanza de las ciencias y cambios tecnológicos: del dilema limitante a la construcción humanizadora en el IF Baiano campus Santa Inês
Keywords: Ensino de ciências; Mudanças tecnológica; Humanização; Exercício curricular; Pesquisa colaborativa; Tecnicismo; Cientificismo; Science teaching; Technological changes; Humanization; Curricular exercise; Collaborative research; Technicalism; Technicalism; Enseñanza de las ciencias; Cambios tecnológicos; Humanización; Ejercicio curricular; Investigación colaborativa; Tecnicismo; Cientificismo; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO